Perencanaan dan Perancangan Youth Center Kota Bekasi Bergaya Arsitektur Dekonstruksi - Retno Fitri Astuti; Harry Miarsono; Lady Christantina (Prosiding Sains dan Teknologi, 2022)
Youth Center is one of the infrastructures that is needed to support youth activities in accommodating and channeling interests and talents as well as increasing self-development, independence, and maturity in youth. However, facilities that are not accommodated properly for youth is the cause of juvenile delinquency, while youth is an essential period to form individual character. As can be seen from the data on the number of population projections, there are quite a lot of youth age categories, but complete facilities and space are not available yet in Bekasi to accommodate positive activities for youth. The location chosen in Summarecon Bekasi which is close to many educational facilities is one of the destinations for youth to gather. Deconstruction Architecture concept building is the right choice to represent youth who are full of high awareness, willing to try new things, unstable, emotional, likes freedom, likes something different, acts without thinking.The concept of the building also greatly affects the attractiveness of youth to come because a supportive atmosphere will give comfortable impression for visitors. Keywords : Youth Center Bekasi City, Summarecon Bekasi, Deconstruction Architecture